2021
DOI: 10.1124/pharmrev.120.000273
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Biology of Phosphodiesterase 4 Enzymes as Pharmacological Targets: An Interplay of Isoforms, Conformational States, and Inhibitors

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 291 publications
2
46
0
Order By: Relevance
“…Alternatively, one could also postulate that a critical role of a particular PDE4 subtype on body temperature may have been obscured in the response of the respective PDE4 knockout mouse by compensatory changes in the expression or activity of the three other PDE4 isoforms. We consider this unlikely, however, given the large body of data suggesting that PDEs are not functionally interchangeable [ 3 , 88 , 89 ] and because such compensatory changes in PDE4 expression were not observed in various primary cells or tissues of PDE4-KO mice reported previously [ 19 , 20 , 22 , 23 , 52 , 61 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Alternatively, one could also postulate that a critical role of a particular PDE4 subtype on body temperature may have been obscured in the response of the respective PDE4 knockout mouse by compensatory changes in the expression or activity of the three other PDE4 isoforms. We consider this unlikely, however, given the large body of data suggesting that PDEs are not functionally interchangeable [ 3 , 88 , 89 ] and because such compensatory changes in PDE4 expression were not observed in various primary cells or tissues of PDE4-KO mice reported previously [ 19 , 20 , 22 , 23 , 52 , 61 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 97%
“…Type 4 cyclic nucleotide phosphodiesterases (PDE4s) comprise a group of four isoenzymes, PDE4A to D, that hydrolyze and inactivate the second messenger cAMP. PDE4s are widely expressed throughout mammalian cells and tissues [ 1 , 2 , 3 , 4 , 5 ], and diverse therapeutic benefits result from their non/PAN-selective inhibition. Preclinical studies of PAN-PDE4 inhibitors have established their potent anti-inflammatory, memory- and cognition-enhancing, anti-depressant and anti-psychotic, metabolic, and cardiovascular properties [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in 1996, it become evident that a better side-effect profile could be obtained with agents preferentially targeting the catalytic site over HARBS [ 65 ]. Then, this type of selectivity was not pursued any longer, and another type of selectivity versus the gene products A-D was proposed after these subtypes were characterized, their tissue distribution demonstrated and their different functional role suggested [ 66 ]. In the early 2000s, the PDE4D isoform was indicated as being responsible for PDE4 inhibitor-induced emesis [ 67 ], although recent studies suggest that it may not be the only factor involved in this side effect [ 68 ]; on the other hand, it has been demonstrated that PDE4B selective inhibitors produce potent anti-inflammatory and reduced emetic effects [ 69 ].…”
Section: From In Vitro and Preclinical Profile Of The First Pde 4 Inh...mentioning
confidence: 99%
“…The approval and clinical use of PDE4 inhibitors for the treatment of major human inflammatory disorders demonstrates the tremendous progress over the last 7 years, with indications expanding at an almost yearly pace. PDE4-selective inhibitors have now been approved for the oral treatment of chronic obstructive pulmonary disease [ 6 ], psoriatic arthritis and plaque psoriasis [ 7 ], and as a topical treatment for atopic dermatitis [ 8 ]; they are also being considered as therapeutics for diseases of the CNS [ 9 , 10 ]. Hence, PDE inhibitors are proving to be of great clinical benefit in inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%